THE BODY IN PAIN ONLINE: EXPLORING DIGITAL AFFECT THROUGH USER-GENERATED SUFFERING - Seko, Yukari (AoIR Selected Papers of Internet Research, 2015)
The Digital Millennium Copyright Act of 1998 (DMCA) signaled that network communication technologies would not yet escape traditional modes of production and consumption of prior communication technologies like books, cassettes, and VCRs. While there are myriad critiques of the DMCA as well as historical and legal analyses of copyright and technology, this paper diagrams a genealogy of the DMCA that differs from yet complements existing literature. Although the DMCA is “digital” in its objects (technologies) and mode (technique) of governance, it is a patchwork of antecedents developed for an through technologies like microfilm, DAT, and VCRs. This paper makes two related claims—one informed by history another informed by theory. First, the history of legislation and technologies leading from about the 1909 Copyright Act to the DMCA indicates that new media technologies do not only offer new ways of infringing copyright but produce entirely new re-imaginings and redefinitions of infringement that are partly technologically-determined. The second, theoretical claim, is that Kittler’s (2010) three functions of media—transmission, storage, processing—offer a robust heuristic for analyzing how the objects and means of governing culture through copyright have evolved over the past century. This latter claim confirms and structures the historical analysis of reimagining infringement.